Prerequisites for the legal mechanisms development to combat disinformation in social media in the context of national security: problem statement - A. I. Marushchak (Bulletin of Kharkiv National University of Internal Affairs)
The article deals with the preconditions for the legal mechanisms development to combat disinformation in social media in the context of national security. The conclusion is formulated on the necessity of the development of such mechanisms on the basis of constitutional freedom of speech principle, with legislative definition of the exclusive possible restriction list in social media for the sake of national security.